Ultrasound-guided coracobrachialis plane musculocutaneous nerve block for perioperative analgesia in pediatric Gartland type III supracondylar humerus fracture: a prospective pilot study - Gao, Tianyi; Song, Zhuorun; Lu, Shunyi; Song, Nan; Yu, Wentao; Yang, Huilin; Zou, Jun; Wang, Qian; Ge, Jun (Frontiers in Pediatrics, 2025)
PurposePerioperative pain management in children with Gartland Type III supracondylar humerus fractures (SHF) is crucial but often inadequately addressed, leading to significant pain experiences. This study aimed to evaluate the efficacy and safety of coracobrachialis plane musculocutaneous nerve block (Cora-MNB) compared to supraclavicular brachial plexus block (SC-BPB) for analgesia in pediatric Gartland Type III SHF patients.MethodsA prospective pilot study enrolled 105 pediatric patients with Gartland Type III SHF was performed. Primary outcome was the postoperative FLACC scale measured at 12 h postoperatively. Secondary outcomes included FLACC scale measured at 1 h, 6 h and 24 h postoperatively. They also included postoperative thumb and shoulder strength, opioid use, NSAIDs use, length of hospital stays, patient satisfaction, surgeon satisfaction, operation time and puncture channels. One hundred and five patients were randomized allocated between groups.ResultsPatients receiving Cora-MNB showed superior analgesia, with median postoperative FLACC pain scores at 12 h reduced by 40% [Cora-MNB: 3.00 (2.00) vs. SC-BPB: 5.00 (2.00), ***p < 0.001]. Thumb extensor weakness incidence decreased significantly (Cora-MNB: 13.5% vs. SC-BPB: 84.9%, ***p < 0.001). Shoulder mobility preservation was achieved in 98.08% of Cora-MNB cases vs. 20.75% with SC-BPB (***p < 0.001). While opioid consumption showed no intergroup difference, Cora-MNB reduced NSAID rescue times [Cora-MNB: 0.00 (1.00) vs. SC-BPB: 1.00 (1.00), **p = 0.0014]. Procedure duration favored Cora-MNB [4.54 ± 1.21 (min) vs. 9.02 ± 1.94 (min), T = 14.32, 95% CI: 3.88–5.12, ***p < 0.001], with higher surgical and parental satisfaction scores. Hospital stays remained comparable [1.60 ± 0.66 (days) vs. 1.56 ± 0.67 (days), p = 0.98].ConclusionCora-MNB proves to be a safe and effective approach for anesthesia in pediatric SHF cases, offering superior analgesic outcomes, reduced NSAIDs usage, improved shoulder functionality, and high satisfaction levels without extending the hospital stay. This study supports the implementation of Cora-MNB as a valuable technique in perioperative pain management for pediatric SHF patients.